Resilience of Women Fishermen's Wives in Pasie Nan Tigo, Kota Padang(Case Study of Women Fish Sellers) - Olfitri, Lovya Mahesya; Putri, Lili Dasa (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The background of this research is women living on the coast of Pasie Nan Tigo who carry out a dual role as a wife and also supplement their income. Women in Pasie Nan Tigo work to increase their income because their husbands' income is not sufficient for household needs. This requires women in Pasie Nan Tigo to be able to work to meet the needs of the family. There is a dual role played by women in Pasie Nan Tigo as figures who are tough and never give up to create a prosperous family and economy. This research uses a qualitative approach with the nature of a case study which aims to provide an overview of the research findings. The location of this research is Pasie Nan Tigo, Padang City. The subjects of this research were female fish sellers, Mrs. ML, Mrs. RS, and also Mrs. YS. The research informants were the people of Pasie Nan Tigo, Mrs. MR and the fisherman in Pasie Nan Tigo, Mr. AR. Data collection techniques use observation, interviews and documentation. Data validity techniques use method triangulation, source triangulation, and theoretical triangulation. The results of the research findings show that the role of women in the family is caring for, educating children, taking care of the household, contributing to increasing income, how women survive by selling fish in the market and having an active strategy for survival, and the resilience of women in carrying out dual roles, namely: tough because she acts as a mother to her children, as a wife to her husband who serves her husband well, and carries out multiple roles without giving up.